The Influence of Service Marketing Mix and the Perception of Corporate Image Affects the Loyalty of Customers of Resort and Homestay in Phetchaburi Province - Wongrat, Kritchana (Community and Social Development Journal, 2020)
This study was aimed at 1) Study the influence of service marketing mix, perception of corporate image and loyalty of customers; 2) Study the influence of service marketing mix that affects loyalty of customers and 3) Study the influence of service marketing mix and the perception of the corporate image that affects loyalty of customers of resort and homestay in phetchaburi province. The research samples were 400 customers selected by using simple random sampling. The research instrument was a questionnaire. The data were analyzed by using frequency, percentage, mean, standard deviation and multiple regression analysis. The research results were as follows: 1) Service marketing mix, the perception of the corporate image and loyalty of customers was totally a high level. 2) Influence of service marketing mix including place, price, promotion and process has a positive effect on loyalty of customers with the level of .01 statistically significance. All of them could predict efficiency of 65.50 percent. and 3) Influence of service marketing mix and corporate image has a positive effect on loyalty of customers with the level of .01 statistically significance. All of them could predict efficiency of 71.20 percent From this research, it was found that the service marketing mix strategy is important for the resort and homestay, which must be development to be of quality to meet the needs and satisfaction of customers. And creating a good image of the business to achieve customer loyalty resulting in frequent re-se of the service.